Calling time on the imperial lawn and the imperative for greenhouse gas mitigation. (6th January 2023) - Gillman, Len N.; Bollard, Barbara; Leuzinger, Sebastian
Abstract : Non-technical summary: As green spaces, lawns are often thought to capture carbon from the atmosphere. However, once mowing, fertlising and irrigation are taken into account, we show that they become carbon sources, at least in the long run. Converting unused urban and rural lawn and grassland to treescapes can make a substantial contribution to reducing greenhouse gas emissions and increasing carbon absorption from the atmosphere. However, it is imperative for governing bodies to put in place appropriate policies and incentives in order to achieve this. Technical summary: Mown grass or lawn is a ubiquitous form of vegetation in human-dominated landscapes and it is often claimed to perform an ecosystem service by sequestering soil carbon. If lawn maintenance is included, however, we show that lawns become net carbon emitters. We estimate that globally, if one-third of mown grass in cities was returned to treescapes, 310–1630 million tonnes of carbon could be absorbed from the atmosphere, and up to 43 tonnes of carbon equivalent per hectare of emissions could be avoided over a two-decade time span. We therefore propose that local and central governments introduce policies to incentivise and/or regulate the conversion of underutilised grass into treescapes. Social media summary: If unused lawns were planted with trees, a gigaton of carbon could be removed from the atmosphere over two decades.